Study of Thermal Conductivity and Solution Absorption for Epoxy –Talc Composites - I. Jaafar, Harith; I. Hussein, Seenaa; M. jaafar, Huda (Iraqi Journal of Science, 2021)
In this research prepared Epoxy – Talc powder composites with weight ratio of Talc powder (0,5,10,15,20,25)% . The value of thermal conductivity increase with increasing ratio of talc powder and water absorption increase with increasing ratio of talc powder because the structure from magnesium silicate hydroxide and hydrophilic nature .Ethanol absorption decrease with increasing percentage talc powder compared with epoxy pure